Research and practices to learn how to reach a sustainable and healthy economic and social recovery post Covid-19 - Paolo Federighi; Francesco De Maria; Giovanna Del Gobbo; Laura Menichetti; Francesca Torlone (Firenze University Press, 2021)
Dopo la pandemia Covid-19: ricerca e pratiche per apprendere percorsi di ripresa economica e sociale sana e sostenibile.